The Analysis of Students Critical Thinking Based on the Concept of Flowmap on Chemical Bond - Azmi, Johni; Rery, R. Usman; Alimin, Masnaini (Proceedings of the UR International Conference on Educational Sciences, 2018)
Education in the 21st century requires students and teachers to master various skills including critical thinking skills. Critical thinking is an aspect that has been researched in recent years with the aim of seeing the thinking skills and cognitive abilities of teachers and students. Therefore this study aims to analyze students critical thinking in answering questions about chemical bonding topic. The sample of this study was 171 high school students in Pekanbaru. Data were analyzed using SPSS 21.0 by looking at the frequency of students in answering questions and elaborating on the answers. The results of the study showed that students were still at a low critical thinking stage based on the frequency of students in explaining and answering the questions given. Based on the results of this study was expected to provided information for teachers to be able to improve cognitive thinking and critical thinking of students and develop a variety of critical thinking questions so that students have a lot of experience in describing problems and understand well the concept of chemical topics.